Zdenek Fibich's Musical Speech in His Concert Melodramas - Loos, Helmut (Musicologica Olomucensia, 2010)
The genre of melodrama occupies an entirely unique place in art history. It has proven to be a singular genre of art throughout its history. Various types of melodrama, such as monodrama, duodrama and concert melodrama, are quite distinct from staged melodrama. Bohemian composers in particular have fostered melodramas; Georg/Jiri Benda is famed for being one of the first successful creators in this genre, and Frantisek Skroup established it in the Czech language as a national form. Its development reaches a climax with Zdenek Fibich's six concert melodramas and Hippodamia, his trilogy of staged melodramas. These works have been designated as ``the culmination of European melodrama'' by Jaroslav Jiranek. This paper discusses how Fibich formulated his concert melodramas, and what their contents reveal about Fibich's position with respect to the politics of art.Translated by Judith Fiehler
Keywords: Zdenek Fibich's melodrama; Art religion in 19th century; music analysis